2023
DOI: 10.1039/d3cp01097j
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic growth of chemical gardens from mixtures of two salts

Abstract: Chemical gardens formed from two metal salts (MCl2 or MSO4) have been investigated to understand mixing effects on the growth of precipitate tubes. The growth of tubes can be classified...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Sodium silicate solution has a density of 2.4 g cm À3 while sodium tungstate solution has a density of 4.18 g cm À3 . An empirical expression (1) representing the relation between the buoyant force and the density of the liquid in the case of the immersed object sinking to the bottom of the container is utilized to obtain insights into the contribution of these physicochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium silicate solution has a density of 2.4 g cm À3 while sodium tungstate solution has a density of 4.18 g cm À3 . An empirical expression (1) representing the relation between the buoyant force and the density of the liquid in the case of the immersed object sinking to the bottom of the container is utilized to obtain insights into the contribution of these physicochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical gardens, which have been known for almost four centuries, are self-organizing architectures of precipitates facilitated by the emergence of semi-permeable membranes under far from equilibrium conditions when a metal salt reacts with an anionic solution. [1][2][3][4][5][6][7][8] Inorganic precipitation and crystallization processes can result in a plethora of evenly curved, often life-like patterns that certainly do not match within the standard array of crystal morphologies. 9,10 A chemical garden architecture is the outcome of osmotic pressure driven forced convection across the semipermeable membrane and buoyancy-driven free convection.…”
Section: Introductionmentioning
confidence: 99%
“…Chemobrionic systems are intricate self-organizing hierarchical architectures primarily consisting of inorganic membranous structures. However, these materials have not yet been employed for any electronic device application. One classic instance of a chemobrionic system is represented by vertically growing tube-like chemical gardens, which were originally documented in 1646 by Glauber.…”
Section: Introductionmentioning
confidence: 99%
“…Amphoteric products, however, can result in thin membranes of constant width . Research on multi-metal and other more complex precipitates has only recently begun. , For example, Wang et al studied precipitate membranes formed from seawater and showed the highly selective precipitation of Mg­(OH) 2 compared to CaCO 3 . Such work is important because the porous walls of vent chimneys are composed of a wide variety of minerals containing Fe, S, Mg, Ca, and Ba as well as trace metals, such as Ni, Co, Mn, Cu, and Zn. Moreover, the steep cross-membrane gradients and overall non-equilibrium conditions in hydrothermal vents are at least partially captured by microfluidic experiments and allow us to study how these conditions affect the average product composition and possible compositional gradients. , …”
Section: Introductionmentioning
confidence: 99%
“…36 Research on multi-metal and other more complex precipitates has only recently begun. 33,37 For example, Wang et al studied precipitate membranes formed from seawater and showed the highly selective precipitation of Mg(OH) 2 compared to CaCO 3 . 33 Such work is important because the porous walls of vent chimneys are composed of a wide variety of minerals containing Fe, S, Mg, Ca, and Ba as well as trace metals, such as Ni, Co, Mn, Cu, and Zn.…”
Section: Introductionmentioning
confidence: 99%